Why real-world health information technology performance transparency is challenging, even when everyone (claims to) want it. (11th September 2020) - Adler-Milstein, Julia; Thao, Crishyashi
Abstract: Crowdsourced ratings have driven increased performance transparency between consumers and suppliers. While many industries have benefitted from such transparency, crowdsourced ratings have struggled to scale in the healthcare domain. In theory, interoperability services offer an ideal setting for crowdsourced ratings: costs are high, performance is variable, and information asymmetries between provider organizations (customers) and vendors offering interoperability solutions exist. Via a Cooperative Agreement between the Office of the National Coordinator for Health Information Technology and University of California, San Francisco, we developed InteropSelect, a public website that allows crowdsourced ratings of interoperability service purchases. While we garnered broad engagement during the development process, the site failed to attract sufficient reviewers, which is fundamental to the success of crowdsourcing. Additional challenges included the lack of service commoditization that resulted in a complex rating form and lack of market dynamics that facilitated vendor engagement. Our lessons cast doubt on whether crowdsourcing and similar performance transparency efforts under the 21st Century Cures Act will succeed.